Evaluating the Impact of Digital Transformation Policies on Transparency and Accountability in Public Governance - Amelia, Reva (IHSA Institute, 2026)
The rapid advancement of digital technology has encouraged governments to adopt digital transformation policies aimed at improving governance, particularly in terms of transparency and accountability. However, the extent to which these policies achieve their intended outcomes remains a subject of debate, especially in developing countries. This study aims to analyze the impact of government digital transformation policies on public transparency and accountability, as well as to identify the factors influencing their effectiveness. The research employs a mixed-methods approach, combining qualitative techniques such as case studies, interviews, and policy analysis with quantitative methods, including public perception surveys and statistical analysis. The findings reveal that digital transformation policies contribute positively to improving transparency by increasing access to government information and enhancing accountability through better monitoring and reporting systems. Nevertheless, these improvements are not fully optimal, as challenges related to data quality, digital literacy, infrastructure limitations, and low public participation persist. The study also identifies a significant gap between policy design and implementation, indicating that digital initiatives often achieve procedural rather than substantive outcomes. In conclusion, while digital transformation policies have strong potential to enhance governance, their effectiveness is highly dependent on institutional readiness, technological capacity, and social engagement. Therefore, a comprehensive and integrated approach is necessary to ensure that digital transformation leads to meaningful and sustainable improvements in public transparency and accountability.